1992
DOI: 10.1523/jneurosci.12-08-02982.1992
|View full text |Cite
|
Sign up to set email alerts
|

Early appearance of and neuronal contribution to agrin-like molecules at embryonic frog nerve-muscle synapses formed in culture

Abstract: Antibodies against chicken and Torpedo agrin were used for immunofluorescent staining in order to assess the spatial distribution and temporal appearance of agrin-like molecules at newly formed synaptic contacts in cultures of embryonic Xenopus nerve and muscle cells. The antibodies stained Xenopus neuromuscular junctions and removed ACh receptor (AChR)-aggregating activity from extracts of Xenopus brain. Immunofluorescence was observed at almost all nerve- induced AChR aggregates, even at microaggregates in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 31 publications
7
49
1
Order By: Relevance
“…Agrin, a synapse-organizing protein, was implicated to be important in directing the formation of these postsynaptic specializations in the developing and regenerating neuromuscular junctions [2~,]. During development, agrin is expressed by motor neurons of the spinal cord [5]; it is released at the sites of contact with developing muscle fibers [6,7] and thus, induces the aggregation of AChRs and other components at the neuromuscular junctions [8]. Anti-agrin antibodies block nerve-induced AChR aggregation in motor neuron-myotube co-cultures [9].…”
Section: Introductionmentioning
confidence: 99%
“…Agrin, a synapse-organizing protein, was implicated to be important in directing the formation of these postsynaptic specializations in the developing and regenerating neuromuscular junctions [2~,]. During development, agrin is expressed by motor neurons of the spinal cord [5]; it is released at the sites of contact with developing muscle fibers [6,7] and thus, induces the aggregation of AChRs and other components at the neuromuscular junctions [8]. Anti-agrin antibodies block nerve-induced AChR aggregation in motor neuron-myotube co-cultures [9].…”
Section: Introductionmentioning
confidence: 99%
“…On cultured myotubes, agrin induces aggregation of several molecules that are concentrated at the NMJ including AChRs (Nitkin et al, 1987;Wallace, 1989). Motor neurons synthesize agrin, transport it to the nerve terminal from where it is released to induce AChR aggregation McMahan, 1988, 1990;Reist et al, 1992;Cohen and Godfrey, 1992).…”
mentioning
confidence: 99%
“…Together, they provide further insights into the molecular mechanisms underlying agrin effects on neurite elongation in central neurons. A potential role for this extracellular matrix protein during neurite outgrowth was first suggested based on its predominant expression during the early stages of development and its subcellular localization in growth cones (Cohen and Godfrey, 1992;Mann and Kroger, 1996;Ferreira, 1999;Serpinskaya et al, 1999;Neuhuber and Daniels, 2003). Functional studies provided additional evidence for a regulatory role of agrin on the rate of axonal and dendritic elongation in central neurons (Chang et al, 1997;Gautman et al, 1996;Ferreira, 1999;Mantych and Ferreira, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This multi-domain glycoprotein is encoded by a single gene that is alternatively spliced to give rise to several isoforms (Deyst et al, 1998;Glass et al, 1996Glass et al, & 1997Godfrey, 1991;Godfrey et al, 1988;Hoch et al, 1994;McMahan, 1990;Ruegg et al, 1992Ruegg et al, & 1998Rupp, et al & 1992Sanes, 1997;Stone and Nikolics, 1995). The neuron-specific isoform was initially detected in motor neurons (Cohen and Godfrey, 1992;Magill-Solc and McMahan, 1988). Later, it was shown that this isoform was also expressed in the brain (Bowe and Fallon, 1995;Hoch et al, 1993;Kroger et al, 1996;Mann and Kroger, 1996;Mantych and Ferreira, 2001;O'Toole et al, 1996;Rupp et al, 1991Rupp et al, & 1992Stone and Nikolics, 1995).…”
Section: Introductionmentioning
confidence: 99%